REKOMENDASI DALAM PENGOPTIMALAN LAJU PRODUKSI MINYAK PADA PENGGUNAAN DUA SUMUR GAS LIFT DENGAN STUDI SENSITIVITAS PROPERTI RESERVOIR DAN INJEKSI GAS - Camara Eka Putra, Derie
Gas lift injection technology has been used for long enough in oil industry as one of artificial lift method. The purpose of the application of this method in the field is to increase oil production because the reservoir pressure is not able to lift the oil to the surface. The optimization problem on gas lift system has become a thing that very concerned in the study artificial lift. Gas injection rate is limited by maximum amount of available gas injection, and liquid production rate is limited by separator capacity. Because of the total gas available in the field is limited, so the volume of gas injectionl plays an important role in determining oil production rate. Oil production rate is a non-linear function of gas injection rate, where unknown explicitly. In its application by using Gas Lift Performance Curve (GLPC) will be known at a certain gas injection conditions will get the most optimum oil rate. In this study, simulations will be done to increase oil production from two wells with gas lift artificial method which is combined using software Pipephase. This research will look for the optimal amount of gas allocation in each well with property sensitivity at gas injection and reservoir. From this study will obtain the relation of gas injection with its property to obtain maximum amount of oil production. In general the results of the analysis show that there are recommendations for certain reservoir properties which are recommended for gas lift method to produce optimum oil rate. In addition, the determination of gas lift properties which will used as gas lift specific gravity, tubing size, and the large of gas injection itself is also strongly influences the oil rate which will be obtained later.